One-pot bio-derived ionic liquid conversion followed by hydrogenolysis reaction for biomass valorization: A promising approach affecting the morphology and quality of lignin of switchgrass and poplar. (December 2019) - Carrozza, Chiara Francesca; Papa, Gabriella; Citterio, Attilio; Sebastiano, Roberto; Simmons, Blake A.; Singh, Seema
Highlights: The choline-based bionic liquids one-pot process converts sugars and recovers lignin. Similar sugar and ethanol yields were observed for switchgrass and poplar. The syringyl/guaiacyl (S/G) ratios affects lignin depolymerization efficiency. Catalytic hydrogenolysis converts lignin from IL-OP to low molecular weight. Abstract: The use of bio-derived ionic liquids (e.g., cholinium lysinate) in a one-pot process was evaluated on overall sugar and lignin yields as a function of two model woody and herbaceous feedstocks, switchgrass and poplar, with emphasis on the study of physical and chemical alterations in lignin structure, by performing a detailed mass balance analysis and chemical characterization. Multiple chromatographic and spectroscopic analytical techniques were applied tracking lignin reactivity and partitioning during the ionic liquid one-pot conversion. Depolymerization efficiency of the lignin-rich residue derived from the whole process was investigated as a function of different temperatures and pressures during catalytic hydrogenolysis by Ni(SO)4 . This study validates the potential of ionic liquid one pot process as an integrated approach for full exploitation of lignocellulosic feedstocks. The insights gained will contribute to the design of future conversion routes for efficient biomass deconstruction and lignin valorization.